2019
DOI: 10.1016/j.lfs.2019.116948
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Ginsenoside Rg1 defenses PC-12 cells against hydrogen peroxide-caused damage via up-regulation of miR-216a-5p

Abstract: Background: Spinal cord injury (SCI) is a destructive trauma accompanying with local injury, half of which cause chronic paralysis. Ginsenoside Rg1 exerts anti-apoptosis and anti-autophagy properties. Therefore, our goal was to study the protective mechanism of Rg1 in attenuating cell injury. Methods: MiR-216a-5p inhibitor was transfected into PC-12 cells, then cells were pre-treated by Rg1 and treated with 300 μ M hydrogen peroxide (H 2 O 2 ) for 24 h. CCK-8 and apoptosis experiments were done to test cell ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Increasing cell proliferation, viability, and motility while lowering apoptosis are all hallmarks of renal carcinomas in which miR-216a-5p is expressed [30]. Recent research has shown that miR-216a-5p has a protective effect against cellular injury [30,31]. A research discovered that upregulating miR-216a-5p, ginsenoside R1 reduced ROSinduced cellular damage, which in turn lowered autophagy and apoptosis in the cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing cell proliferation, viability, and motility while lowering apoptosis are all hallmarks of renal carcinomas in which miR-216a-5p is expressed [30]. Recent research has shown that miR-216a-5p has a protective effect against cellular injury [30,31]. A research discovered that upregulating miR-216a-5p, ginsenoside R1 reduced ROSinduced cellular damage, which in turn lowered autophagy and apoptosis in the cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that miR-216a-5p has a protective effect against cellular injury [30,31]. A research discovered that upregulating miR-216a-5p, ginsenoside R1 reduced ROSinduced cellular damage, which in turn lowered autophagy and apoptosis in the cells [31]. Furthermore, in an asthma model study, miR-216a-5p appears to protect H 2 O 2 -damaged cells by controlling the high mobility group box 1/NF-kB pathway [32].…”
Section: Discussionmentioning
confidence: 99%
“…To further clarify the mechanism, the PI3K inhibitor LY294002 was used to prove that the anti-apoptotic effect was achieved through the PI3K/Akt signaling pathway. Similarly, Rg1 exerts neuroprotection via the same pathway as Rb1 ( Yi et al, 2019 ).…”
Section: Anti-apoptotic Propertiesmentioning
confidence: 99%
“…1A). According to a previous experiment (16), 300 µM was selected as the final dose of H 2 O 2 for the SCI model in view of the appropriate degree of cell death under this dose. Additionally, the viability of PC12 cells treated with different doses of LEN revealed no significant difference compared with the control group (Fig.…”
Section: Len Increases the Viability Of H 2 O 2 -Stimulated Pc12 Cellsmentioning
confidence: 99%